HUBUNGAN PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) DENGAN KEJADIAN DIARE PADA BALITA DI PUSKESMAS CIPONDOH KOTA TANGERANG TAHUN 2022 - Meli Herawati (Nusantara Hasana Journal, 2022)
Diarrhea is a public health problem, especially in toddlers. Indonesia is one of the developing countries that has high diarrhea morbidity and mortality. Diarrhea can be prevented if the community applies clean and healthy lifestyle (PHBS). Objective to determine the relationship between clean and healthy living behavior with the incidence of diarrhea in children under five at the Cipondoh Public Health Center, Tangerang City in 2022. The design in this study used a cross sectional approach. Samples were taken using the Slovin formula with a total sample of 279 respondents. Sampling using simple random sampling technique. This study uses univariate analysis and bivariate analysis using Chi Square test. Based on the univariate analysis of 279 respondents, most of them simply applied PHBS at home with a result of 274 respondents (98.2%) and the incidence of diarrhea in children under five in the last 3 months with a result of 182 children (65.2%). Bivariate results with Chi Square test obtained p-value 0.001 so it can be concluded that there is a relationship between clean and healthy living behavior (PHBS) with the incidence of diarrhea in toddlers. It was found that there was a relationship between clean and healthy living behavior with the incidence of diarrhea in children under five at the Cipondoh Public Health Center, Tangerang City.